CP3 Progressive ataxia with unusual radiographic findings. Issue 11 (22nd October 2010) - Marshall, C; Giovannoni, G
Abstract : A 72-year-old woman presented with a 2-year history of slowly progressive ataxia, accompanied by 13 kg weight loss. MRI imaging of the brain revealed T2-weighted hyperintensities in the pons, midbrain and cerebellum. Multiple blood and CSF investigations for metabolic, inflammatory, infective and genetic aetiologies were negative or normal. A paraneoplastic cause was sought. CT revealed circumferential sheathing of the thoracic and abdominal aorta by abnormal soft tissue. The right kidney was enlarged, with perinephric enhancement and stranding. There were sclerotic bone lesions in multiple ribs, the left humeral midshaft, and both iliac blades. Coarsening of the trabecular pattern was seen in the proximal femurs. Technetium bone scanning showed increased uptake in the sclerotic lesions, and in a symmetrical diametaphyseal pattern in the distal femurs and proximal tibiae. These imaging findings were recognised to be pathognomonic for Erdheim Chester disease, a rare non-Langerhans histiocytosis. The diagnosis was supported by biopsy of the periaortic soft tissue. Progressive ataxia has been described in Erdheim Chester due to infiltration of the cerebellum by histiocytes, but never as the presenting feature. This patient went on to develop other manifestations of histiocytosis, including pituitary, cardiac and pulmonary involvement. Treatment with interferon-α was initiated.